A Blind assistance and navigation system using SIFT algorithm for indoor environments - Zereen, Aniqua Nusrat; Kabir, Sadia Binte (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2013.